Exploring Compact Symmetric Objects with Complex Morphologies - E. E. Sheldahl; G. B. Taylor; S. E. Tremblay; W. Peters; S. Kiehlmann; R. D. Blandford; M. L. Lister; T. J. Pearson; A. C. S. Readhead; F. Schinzel; A. Siemiginowska; R. Skalidis (The Astrophysical Journal, 2025)
Compact symmetric objects (CSOs) are a unique class of jetted active galactic nuclei defined by subkiloparsec radio emission, showing radio structure on both sides of the central engine. CSOs tend to exhibit little to no relativistic beaming, thereby allowing us to determine their physical characteristics, such as the magnetic field strength and particle energy density. Selected with a literature search, we describe very long baseline interferometry observations, imaging, and analyses of 167 CSO candidates. We identified 65 new bona fide CSOs, thus almost doubling the number of known bona fide CSOs to 144. With our greater breadth of sources, we confirm that edge-dimmed CSOs (CSO-1s) may represent a more diverse population than originally expected. We highlight a number of CSOs with complex morphologies, including candidates for supermassive binary black holes and CSOs that appear to have morphologies akin to wide-angle tail galaxies, which could perhaps indicate that some CSOs are experiencing a galactic merger.